Implementasi Kebijakan Pembentukan Peraturan Perundang-Undang dalam Penyusunan Peraturan Desa di Kabupaten Purworejo Provinsi Jawa Tengah - Heni Susila Wardoyo (Jurnal Penelitian Hukum De Jure, 2025)
This study examines the implementation of legislation formulation policy in the drafting of Village Regulations (Perdes) in Purworejo Regency, Central Java Province, with a focus on the involvement of Legislative Drafters (Perancang Peraturan Perundang-undangan or PUU). Purworejo Regency was chosen because it presents complex dynamics of village development and serves as a case study to illustrate the implementation gap between national, regional, and village-level policies in the context of village regulations. Although Article 98 of Law Number 12 of 2011 mandates the participation of drafters at every stage of regulation drafting, implementing regulations such as the Ministry of Home Affairs Regulation (Permendagri) Number 111 of 2014 have yet to accommodate this provision. This research adopts an empirical legal approach using qualitative methods and Grindle's policy implementation theory as the main analytical framework, encompassing the dimensions of content of policy and context of implementation. Data were collected through interviews with nine key actors from the village to the national level and document analysis. The findings reveal that the policy implementation, such as the lack of clarity in regulatory objectives, limited technical resources, and poor legal substance quality, stems from the absence of PUU drafters. Moreover, institutional fragmentation, inadequate regulatory support, and restricted access to structured legal assistance further hinder the policy implementation. The Strengths, Opportunities, Aspirations, and Results (SOAR) approach was employed to formulate an optimal strategy. Three-phase strategies are proposed: development of a digital platform for PUU drafter engagement (short term), revision of Permendagri 111/2014 (medium term), and amendment of Law Number 12 of 2011 (long term). The core conclusion of this study is that the systemic involvement of Legislative Drafters (PUU) is essential to optimize the implementation of legislation drafting policy at the village level.